CULTURAL NEGOTIATION THROUGH COMMODIFICATION AND INTERCULTURAL COMMUNICATION IN NYAWANG BULAN IN KASEPUHAN BUNISARI - Shalsa Billa Fadillah (PT. Jurnal Center Indonesia Publisher, 2026)
The Nyawang Bulan tradition in Kasepuhan Bunisari, Girimekar Village, Bandung Regency faces challenges of preservation amid modernization and cultural tourism. The local community must balance maintaining the historical and spiritual values of the tradition with the economic and entertainment demands of tourists. This research problem focuses on how the process of cultural commodification affects the meaning of the tradition, as well as how intercultural communication strategies are employed by the community to convey cultural values to diverse audiences. This study aims to analyze the relationship between cultural commodification and intercultural communication practices in the Nyawang Bulan tradition, as well as to identify adaptation strategies implemented by the community to preserve the core meaning of the tradition. The research employs a descriptive qualitative approach with a post-positivist paradigm. Data were collected through participant observation, in-depth interviews, and documentation, and then analyzed using the Miles and Huberman model. The results indicate that the Nyawang Bulan tradition undergoes a process of commodification through artistic performances, cultural markets, and digital branding, allowing local culture to be consumed more widely without losing its fundamental meaning. Intercultural communication strategies, including message and symbol accommodation, enable tourists to understand the values of the tradition while maintaining local identity. The tradition serves as an adaptive space for cultural dialogue, integrating preservation, cross-cultural interaction, and community economic empowerment.